2021
DOI: 10.18786/2072-0505-2021-49-009
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance tractography based on the constrained spherical deconvolution in patients with gliomas of the optic pathway

Abstract: Background: The use of magnetic resonance (MR) tractography in neurosurgery is becoming an increasingly common practice for noninvasive imaging of white matter pathways. The most common method of tract reconstruction is the deterministic algorithm of diffusion tensor magnetic resonance imaging (MRI). However, this method of reconstructing pathways has a  number of significant limitations. The most important of them are the lack of the possibility of visualizing the intersecting fibers, the complexity of buildi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…According to K. Schilling and coauthors (Schilling et al 2019), a similar number of fibers were false positive in HARDI CSD tractography with the settings similar to those used in our work. Our previous experience in fiber tracking demonstrated that false-positive fibers usually did not form thick bundles (Baev et al 2021) and that the brightness of the tractogram voxels for falsepositive fibers tended to be low.…”
Section: False Positive Tract Removal Splitting the Patient Tract Masksmentioning
confidence: 99%
“…According to K. Schilling and coauthors (Schilling et al 2019), a similar number of fibers were false positive in HARDI CSD tractography with the settings similar to those used in our work. Our previous experience in fiber tracking demonstrated that false-positive fibers usually did not form thick bundles (Baev et al 2021) and that the brightness of the tractogram voxels for falsepositive fibers tended to be low.…”
Section: False Positive Tract Removal Splitting the Patient Tract Masksmentioning
confidence: 99%
“…Алгоритм FACT получил распространение вследствие высокой информативности, простоты проведения и постобработки. С помощью этой модели в каждом вокселе возможно оценить только одно направление волокна [1]. Однако ранее было доказано, что до 90 % вокселей белого вещества в головном мозге содержат пересекающиеся волокна [13].…”
Section: продолженное медицинское образованиеunclassified